Effect of Priming Treatment on Improving Germination and Seedling Performance of Aged and Iron-Coated Rice Seeds Aiming for Direct Sowing - Nasratullah Habibi; Parneel; Naoki Terada; Babil Pachakkil; Atsushi Sanada; Atsushi Kamata; Kaihei Koshio (Plants)
In the case of direct sowing of rice in Japan, cold stress is a critical constraint affecting seed germination and early seedling development, ultimately reducing crop productivity. We evaluated the effects of priming, with or without iron coating on the germination and vigor of rice seeds harvested in 2022, 2023, and 2024. The assessments were conducted at seven temperature conditions: 13 °C, 15 °C, 17 °C, 19 °C, 21 °C, 23 °C, and 25 °C. Seeds were primed with or without PEG6000; coated with or without a mixture of calcined gypsum and iron powder; and tested for germination percentage, germination speed, and seedling vigor index. Under optimal conditions, iron-coated seeds harvested in 2022 showed a significant increase in germination from 58% (non-coated without priming) to 76% (coated with priming), and the seedling vigor index improved from 615 to 890. Under cold stress (15 °C), the coated seeds of the same year achieved 68% germination with priming compared to 46% in non-coated seeds without priming, with a vigor index increase from 480 to 750. Similar improvements were observed in seeds from 2023 and 2024, although the effect was more prominent in older than younger seeds. These results indicate that iron seed coating in combination with PEG priming mitigates the negative impacts of seed aging and enhances tolerance to cold stress during germination. The technique offers a promising, low-cost approach to improving rice establishment in environments facing suboptimal seed storage and early-season cold temperatures, in particular, aiming for direct sowing methods.